Preparation And Properties Of Rubber Seed Shell Flour (Rssf)Filled Polypropylene (Pp) Composites - Shafiq, Mohamad Danial (2014)
In this research, rubber seed shell flour (RSSF) was incorporated in polypropylene (PP) to determine the composites with optimum properties. RSSF loadings were varied from 10 php to 40 php to study the effect of adding RSSF on processing, tensile, morphological, flexural, impact, water absorption and thermal properties of PP/RSSF composites. In the second series, the effect of adding polyethylene copolymerized with acrylic acid (PE-co-AA) was studied, on the properties of PPIRSSF composites. Phthalic anhydride (PA) was added as a compatibilizer separately in PPIRSSF composites in the third series. In the next series, epoxidized vegetable oil (EVO) was added as a compatibilizer in PP/RSSF with fixed amount of 7 php. Preparation of the composites has been conducted in Haake Polydrive internal mixer with the temperature of 180°C using rotor speed of 50 rpm. The addition of RSSF in the composites increased the stabilization torque in PP composites. Furthermore, compatibilization of PPIRSSF composites with PE-co-AA and p A increased the stabilization torque of PPIRSSF. Somehow, the presence of EVO reduced the stabilization torque resulted from flexible and long chain of EVO. The addition of RSSF in PP reduced the tensile strength and elongation at break, somehow, the Young's modulus is improved. This is mainly caused by incompatibility of PP and RSSF resulted to poor interfacial adhesion. Clear observations were presented in SEM micrograph of tensile fracture surface. The incorporation of RSSF in PP has increased the water absorption of the composites xxiv due to the presence of lignocelluloses in RSSF, which possibly creates hydrogen bonding with water.